Procedure for Using Crystalloid and Colloid Fluids in Blood Pressure in Sectio Caesaria Patients Using Spinal Anesthesia Technique - Sanjaya, Dwi Arymbhi; Agustini, Ni Luh Putu Inca Buntari; Putra, I Gede Agus Shuarsedana; Lewar, Emanuel Ileatan (JURNAL KESEHATAN PRIMER, 2018)
Background: In Indonesia, the study about effectivity and side effect of colloid and crystalloid fluid have been completed, but the study about standard operating procedures (SOP) never have been done. The aim of this research was to describe and evaluate the SOP for the use of crystalloid and colloid fluids on blood pressure in sectio caesarea by using spinal anesthesia techniques. Method: The research employed a descriptive quantitative method by using a questionnaire. The basic features of crystalloid and colloid fluid selection were analyzed by multiple response tests. This research was conducted in type A hospitals in the Denpasar area by involving 30 anesthesiologist as a respondent. Result: The results indicated that 76.7% of respondents stated that there was no SOP for crystalloid and colloid fluids to prevent maternal hypotension in sectio caesarea by using spinal anesthesia techniques. In the multiple response tests, the effectiveness and side effects (21.3%) were the factors that had to be considered in the crystalloid and colloids fluid selection to prevent maternal hypotension in sectio caesarea by using spinal anesthesia techniques. The National Guideline of Medical Services for Anesthesiology and Incentive Therapy have been followed in determining the use of crystalloid and colloid fluids at section Caesarea. However, the guideline did not explain the basis for selecting crystalloid and colloid fluids to prevent maternal hypotension in sectio caesarea by using spinal anesthesia techniques in more detail, therefore the factors of effectiveness and risk of side effects are the main consideration.